2020
DOI: 10.1016/j.asmr.2020.07.004
|View full text |Cite
|
Sign up to set email alerts
|

High Variability in Functional Outcomes and Recurrences Between Contact Sports After Arthroscopic Bankart Repair: A Comparative Study of 351 Patients With a Minimum 3-Year Follow-Up

Abstract: Purpose To compare return to sports, functional outcomes, and complications of a consecutive series of contact athletes with anterior glenohumeral instability treated with isolated arthroscopic Bankart repair for isolated anterior instability. Methods Between January 2008 and December 2016, 351 competitive athletes who participated in contact or collision sports underwent isolated arthroscopic Bankart repair at our institution (rugby n = 105, soccer n = 90, martial arts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…The ASOSS score varied significantly between sports (P < 0.001) [16]. there is great variability in the rate of return to sport at the same level, in shoulder performance after returning to competition, and in the postoperative recurrence rates [16]. This is similar to our findings where the Rowe scores showed statistical improvement after operation with P <0.001.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The ASOSS score varied significantly between sports (P < 0.001) [16]. there is great variability in the rate of return to sport at the same level, in shoulder performance after returning to competition, and in the postoperative recurrence rates [16]. This is similar to our findings where the Rowe scores showed statistical improvement after operation with P <0.001.…”
Section: Discussionsupporting
confidence: 86%
“…The mean time to return to sports in the study by Rossi LA was 5.3 months [16]. This is similar to return to full duty in 6 months by the patients studied in this study.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Although much literature in relation to anterior shoulder instability in collision athletes focuses on athletes partaking in American football, hockey, and rugby, Gaelic Athletic Association (GAA) games such as Gaelic football and hurling are collision sports claimed to be the most commonly played sports on the island of Ireland. 2 , 10 , 22 , 25 However, GAA games have increasing popularity with over 400 clubs established worldwide outside of Ireland, leading to over 50,000 registered GAA players in the United States alone. 26 In their previous study, Clesham and Shannon reported excellent functional outcomes with a moderate recurrence rate after ABR in 31 GAA athletes at medium-term follow-up.…”
mentioning
confidence: 99%